Numerical Analysis of Fluid Flow and Heat Transfer in Wavy and Hybrid-Slit-Wavy Fin-and-Tube Heat Exchangers. (3rd July 2019) - Mohanta, Lokanath; Joardar, Arindom; Esformes, Jack L.; Videto, Brian; Sienel, Tobias H.
Abstract : This numerical study pertains to characterizing flow and heat transfer interactions for an interrupted fin design with wavy profile in a compact tube-and-fin heat exchanger. Sinusoidal wavy fin is combined with slit fins to investigate thermal-hydraulic performance relative to an uninterrupted fin design. This fin is referred to as hybrid-slit-wavy (HSW) in this work. Commercial computational fluid dynamics (CFD) software is used for 3D numerical solution of the complete Navier–Stokes and energy equations in the heat exchanger to study flow physics and predict performance. The modeling approach is first validated with available test data from the literature on a wavy (herringbone profile) fin heat exchanger. The predicted friction factor f was within 12% and the Colburn j -factor was within 7% of the reported test data over a Reynolds number range of 350 to 6500. In the case of the HSW fin, it was found that the air-side heat transfer is enhanced by about 20% to 39% relative to the baseline uninterrupted fin with an associated pressure drop penalty of 20% to 38%. The area goodness factors of the HSW fins are up to 4% higher compared to the wavy fins at various operating conditions, indicative of favorable tradeoff.